User acceptance of speed assistance systems: Design guidelines for in-vehicle nudges to influence speeding behaviour - Ekholm, Evelina; Garp, Joanna (My University, 2020)
Speed is a contributor to traffic fatalities and a critical factor in addressing traffic safety. As from 2022, all newly produced vehicles in Europe are required to include Intelligent Speed Assistance (ISA). A key element to efficiently address speeding behaviour is the acceptance of the intervention or strategy employed, which is a concern regarding existing ISA solutions. This master thesis was initiated to investigate how in-vehicle HMI nudges could be applied to an Intelligent Speed Assistance system and what factors in the interaction that should be considered for user acceptance. The project consisted of three phases of analysis, concept development and evaluation that iteratively derived problems and user needs for the interaction with a speed assistance system. Information was gathered through literature studies and qualitative user research. The first phase was concluded in a contextual framework defining the problem and implications of a constantly changing use context where the motivation to comply with the speed limits depends on several critical factors. In the second phase, the contextual framework was used for the concept development in two iterations. This resulted in four final concepts with a common foundation for an ISA system combined with four different spark nudges, aiming to motivate drivers to comply with the speed limits. The four concepts were evaluated with drivers to investigate needs for user acceptance further. The project deliverable was a set of design guidelines with focus on user acceptance for speed assistance systems. The guidelines were divided into categories that address intensity, tolerance, feedback, control and incentives. The categories were found essential for the interaction with a speed assistance system to be accepted and credible among drivers. The project concluded that the HMI (Human-Machine Interface) of a speed assistance system should have an intensity and tolerance that corresponds to drivers’ interpretation of the violation. The value of the feedback provided by the system was also of importance, where the feedback should support the driver in the driving task. It was further found critical that the driver experiences control over the system as it should not act to counteract the driver. It was lastly determined that a system could benefit from being complemented with HMI that utilise existing motivation or create new incentives, to increase the acceptance of an ISA system.